PERSEPSI PETANI TERHADAP PERAN PENYULUH PERTANIAN DI DESA RASI KECAMATAN RATAHAN KABUPATEN MINAHASA TENGGARA - Meksy V. G. Timbulus; Mex L. Sondakh; Grace A.J. Rumagit (Sam Ratulangi University, 2016)
The purpose of this study was to determine the perception of the role of farmers in the village agricultural extension Rasi, District Ratahan, Southeast Minahasa Regency. The study was implemented for 4 months, namely from March to June 2016. This study uses primary data and secondary data. The primary data obtained through interviews with farmers based on a list of questions (questionnaire), while secondary data obtained from the Office of Agricultural Extension Agency for Fisheries and Forestry (BP3K), District Ratahan, Southeast Minahasa Regency. The sampling method in this study is using a non-probability. Analysis of data using a Likert Scale based on the answers of 25 questions to measure the perception of the role of farmers to extension workers with total respondents as many as 36 people. These results indicate that the total score of the level of farmers' perceptions of the role of agricultural extension for 3678 and are in the perception index of 81 percent, thus the perception of farmers as very good. Perception is in excellent farmers also on an indicator of increased productivity results, level of innovation ease of extension can be easily put into practice, the results of innovation extension can be easily seen or observed, productivity increased output is larger than before farmers using agricultural extension innovation.